Correction: RUNX1B Expression Is Highly Heterogeneous and Distinguishes Megakaryocytic and Erythroid Lineage Fate in Adult Mouse Hematopoiesis. - Julia E Draper; Patrycja Sroczynska; Olga Tsoulaki; Hui Sun Leong; Muhammad Z H Fadlullah; Crispin Miller; Valerie Kouskoff; Georges Lacaud (PLoS Genetics)
[This corrects the article DOI: 10.1371/journal.pgen.1005814.].